Primary Prevention of Cardiovascular Events with Aspirin: Toward More Harm than Benefit—A Systematic Review and Meta-Analysis - Christiansen, Mikael; Grove, Erik Lerkevang; Hvas, Anne-Mette (Seminars in Thrombosis and Hemostasis, 2019)
Primary prevention of cardiovascular events with aspirin remains controversial, as the risk of bleeding might outweigh the benefits. Recently, new evidence has emerged from the ARRIVE (Aspirin to Reduce Risk of Initial Vascular Events), ASCEND (A Study of Cardiovascular Events in Diabetes), and ASPREE (Effect of Aspirin on Cardiovascular Events and Bleeding in the Healthy Elderly) trials. The aim of this study was to perform a systematic review and meta-analysis of aspirin's efficacy and safety in the primary prevention of cardiovascular events in healthy individuals and in individuals with cardiovascular risk factors, and separately in those with diabetes. The Medline database was searched, without time restrictions, for relevant human trials published in English up to December 10, 2018, and additional trials were identified from reference lists. Data on efficacy (cardiovascular death and nonfatal myocardial infarction) and safety (major bleeding) were extracted for analysis. In total, 20 randomized trials were identified. Separate meta-analyses were performed on 10 trials including 144,930 individuals, who were healthy or had cardiovascular risk factors, and on 4 trials including 20,326 individuals with diabetes. In healthy individuals and individuals with cardiovascular risk factors, aspirin reduced the risk of nonfatal myocardial infarction by 21% (p < 0.001), but had no effect on cardiovascular death (p = 0.52), and increased the risk of major bleeding by 48% (p < 0.001). In individuals with diabetes, aspirin had no effect on nonfatal myocardial infarction (p = 0.93) or cardiovascular death (p = 0.92) and increased the risk of bleeding by 49% (p = 0.13). This meta-analysis suggests that aspirin should not be used on a routine basis in the primary prevention of cardiovascular events, especially in individuals with diabetes.
Keywords: aspirin; primary prevention; cardiovascular events; safety; diabetes; myocardial infarction